2020
DOI: 10.3389/fvets.2020.00079
|View full text |Cite
|
Sign up to set email alerts
|

Stereotypic Behavior in Sows Is Related to Emotionality Changes in the Offspring

Abstract: Some effects of expressing stereotypic behavior have not yet been elucidated. During gestation, the environment has the potential to interfere with offspring development and to have prenatal or longer-term consequences. We tested the hypothesis that the occurrence of stereotypic behavior during gestation could affect the phenotype of the offspring. Twenty-eight pregnant sows were studied by comparing two groups differing in the amount of stereotypy shown. We analyzed emotionality in the offspring from sows sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 44 publications
0
18
0
2
Order By: Relevance
“…In other words, the higher cortisol concentration in sham-chewing sows could result from a placenta holding this glucocorticoid and protecting the brain development in their offspring. We also have some evidence that the epigenome in the limbic system of these piglets is differentially methylated (45).…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…In other words, the higher cortisol concentration in sham-chewing sows could result from a placenta holding this glucocorticoid and protecting the brain development in their offspring. We also have some evidence that the epigenome in the limbic system of these piglets is differentially methylated (45).…”
Section: Discussionmentioning
confidence: 80%
“…We have shown in preliminary results that the expression of sham-chewing by the mother affects the offspring's emotionality (45). However, in that experiment, we considered a gradient of sows, in which we divided 28 sows in two groups, from low to high expression in terms of duration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have indicated that the management of pigs during gestation promotes changes in their offspring’s behavior [ 38 , 73 , 75 , 106 ]. However, to the best of our knowledge, stressful events in pig farming, such as the effect of gestation crates, lameness, and social isolation have not been explored by epigenetic studies in pigs [ 107 , 108 ].…”
Section: Epigenetics Studies In the Porcine Modelmentioning
confidence: 99%